To Investigate the Effect of Dyslipidemia and Metabolic Function in Coronary Heart Disease with Type 2 Diabetes Mellitus—In the Tertiary Care Center. A Study Protocol - Akansha Singh; Ranjit S. Ambad; Roshan Kumar Jha; Rakesh Kumar Jha (Journal of Pharmacy and Bioallied Sciences)
Introduction: Type 2 DM is the most common type of diabetes and it is characterized by a combination of insulin resistance and relative insulin shortage caused by pancreatic beta cell failure. In India, type 2 diabetes affects 2–4% of the rural population and 4–11.03% of the urban population (urban areas). Due to the accumulation of lipoproteins and cholesterol, it forms plug-in veins and it would cause coronary heart disease. CHD is considered a strong risk issue with the presence of various factors, such as HDL, VLDL, and LDL and blood pressure with their age of patients. Fatty acid from adipose tissue enters the liver, where it is converted to acetyl Co A, which then becomes VLDL. Material and Methods: This would be a cross-sectional study consisting of 100 subjects; distributed into two groups: a) 50 would be type 2 DM with CHD patients, and b) 50 would be nondiabetic with CHD patients. Estimation of the blood sugar level, HbA1c, lipid profile, non-HDL-C and non-LDL-C, insulin resistance, cardiac markers, AST, and ALT were observed. Conclusion: To compare outcome in diabetic and nondiabetic patients with CHD in the eastern region of Maharashtra in the tertiary care center with respect to postoperative morbidity, early mortality, and long-term survival. The present study will be helpful to reveal the heightened risk of CHD in type 2 DM patients due to dyslipidemia and metabolic disorders, emphasizing the need for targeted prevention and management strategy.